Transient Foxp3(+) regulatory T-cell depletion enhances protective Th1/Th17 immune response in murine sporotrichosis caused by Sporothrix schenckii - Batista-Duharte, Alexander [UNESP]; Téllez-Martínez, Damiana [UNESP]; de Andrade, Cleverton Roberto [UNESP]; Polesi, Marisa Campos [UNESP]; Portuondo, Deivys Leandro [UNESP]; Carlos, Iracilda Zeppone [UNESP] (Elsevier, 2020)
The role of regulatory T cells (Tregs) on protective immunity in fungal infections, is controversial. Sporotrichosis is an emerging and worldwide-distributed subcutaneous mycosis caused by various related thermodimorphic fungi of the genus Sporothrix. Previously, we showed an elevated percent of Tregs around 21 days post-infection (dpi) in C57BL/6 mice infected with either Sporothrix schenckii or Sporothrix brasiliensis, but the effect of these cells in the ongoing infection was not evaluated. Here, we aim to characterize the role of Foxp3+ Tregs in a subcutaneous S. schenckii infection model. The flow cytometric analyses showed that S. schenckii infection elicited an expansion of a splenic CD4+Foxp3+ population, including a subset of Helioslow+ after ex vivo stimulation with S. schenckii-heat killed yeast. Depletion of Tregs in DEREG mice revealed a reduction of fungal burden in the skin and systemically in liver and kidneys, associated with enhanced Th1 and Th17 responses. Altogether, our results reveal for the first time that Tregs depletion in ongoing S. schenckii infection improves the protective antifungal immunity and these data suggest that Tregs modulation could be explored as a potential therapeutic strategy in sporotrichosis.
Keywords: DEREG mice; Foxp3; Helios; Regulatory T cells; Sporothrix schenckii; Sporotrichosis